2019
DOI: 10.3390/app9040711
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Active Structural Path for Vibration Reduction Control of Plate Structure under Sinusoidal Excitation

Abstract: The engines of electric and hybrid vehicles cause vibration and noise with complex frequency spectra. This tendency is observed especially for mid-frequency components. Therefore, there are limitations in achieving vibration attenuation using only structural changes, which is the conventional isolation method. A smart structure-based active engine mounting system is a core technology that can continuously improve the noise, vibration, and harshness performance under various operating conditions by continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…An active engine mount system with a hydraulic actuator is designed and controlled by an adaptive controller. The results show that the proposed method can effectively reduce vibration 14 . Passive and active components combined with a sliding mode controller show good control performance in a wide frequency range from 20 Hz to 1 kHz 15 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…An active engine mount system with a hydraulic actuator is designed and controlled by an adaptive controller. The results show that the proposed method can effectively reduce vibration 14 . Passive and active components combined with a sliding mode controller show good control performance in a wide frequency range from 20 Hz to 1 kHz 15 .…”
Section: Introductionmentioning
confidence: 92%
“…An adaptive controller for Active Engine Mount (AEM) is proposed according to the dynamic characteristics of hydraulic engine mount. Experiments have shown that the proposed system can reduce the force transmitted through the AEM 14 . A novel active mount using piezoelectric stack actuators and rubber elements is designed.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, Hong and Kim [19] conducted an analytical investigation on a mounting system that included a PZT stack actuator and rubber mount on a vehicle model with a plate structure and then also utilized one active mount and two rubber mounts; their findings verified the suitability of the system. In addition, Hong and Kim [20] developed a quantification technique to identify the best inputs for active structural routes analytically. The derived inputs must be adjusted through experimentation; however, they perform well numerically.…”
Section: Literature Searchmentioning
confidence: 99%
“…Applying the excitation and control forces to the mount coordinate model yields a response at each location. Equation (20) displays each position response.…”
Section: Secondary Pathway Input Quantificationmentioning
confidence: 99%
“…Hong and Kim [19] analyzed a mounting system comprising three mounts, including one active path, along with the combination of a piezoelectric stack actuator and a passive mount on a plate-structured automotive model. Hong and Kim [20] devised a quantification method for analytically determining the optimal inputs for active structural trajectories. Numerically, the derived inputs performed admirably, but they may benefit from some experimental tuning.…”
Section: Review Of Previous Workmentioning
confidence: 99%